Effectiveness of Self-Assessment with Google Forms to Improve Student Understanding in Biology Learning - Akmala, Muthia; Vidiastuti, Yunilla; Pusparini, Fitria; Safitri, Dini; Ristanto, Rizhal Hendi (Bioedunis Journal, 2024)
This study aims to develop and implement self-assessment based on the Rating Scale method using Google Form in learning Biology, especially on the material of substance movement through cell membranes. The research method used a Research and Development (RD) with the 4D model, involving 33 grade XI students at SMA Negeri 36 Jakarta. Data collection techniques included questionnaires to gather student responses and feedback. Data analysis was conducted using validity and reliability tests, where the instrument demonstrated high validity (r-value r-table value of 0.344) and a reliability coefficient of 0.8667, ensuring consistent and accurate evaluation results. The self-assessment instrument measured students' understanding of concepts such as diffusion, osmosis, and active transport, while also identifying learning barriers. Results revealed that 9.1% of students faced challenges in understanding the topic, with 3% struggling specifically with diffusion. The use of Google Form provided accessibility, ease of use, and efficiency in data analysis. This approach not only encouraged active reflection and independent strategy design among students but also proved adaptable for other Biology topics and technology-based learning contexts.Keywords: biology; movement of substances; self-assessment; rating scale; understanding